ATMPH 2019
DOI: 10.36295/asro.2019.221115
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity, screen time, and nutritional status in adolescents in Banyumas

Abstract: Background:The prevalence of obese adolescents is increasing rapidly followed by an increase in the prevalence of screen time activities. Excessive screen time is related to the consumption of foods that are high in energy and fat and lack of physical activity which results in a positive energy balance resulting in weight gain in adolescents.Objective: To find out the relationship between physical activity and screen time with macronutrient intake and nutritional status in adolescents. Method:The study design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 16 publications
(16 reference statements)
1
1
1
Order By: Relevance
“…For example, 35.3% of early adolescents with high screen time had overweight and obese issues, and so did 30.3% of middle adolescents and 40% of late adolescents. The results differ from other previous studies that showed a significant relationship between screen viewing behavior and nutritional status and between the duration of electronic device (gadget) use and nutritional status [16,22]. Despite the aforementioned findings, previous studies and this current study also posed some weaknesses as they did not consider the covariate factors of physical activity, food intake, and sleep duration that could affect nutritional status [23,24].…”
Section: Relationship Between Screen Viewing Behavior and Nutritional...contrasting
confidence: 99%
See 2 more Smart Citations
“…For example, 35.3% of early adolescents with high screen time had overweight and obese issues, and so did 30.3% of middle adolescents and 40% of late adolescents. The results differ from other previous studies that showed a significant relationship between screen viewing behavior and nutritional status and between the duration of electronic device (gadget) use and nutritional status [16,22]. Despite the aforementioned findings, previous studies and this current study also posed some weaknesses as they did not consider the covariate factors of physical activity, food intake, and sleep duration that could affect nutritional status [23,24].…”
Section: Relationship Between Screen Viewing Behavior and Nutritional...contrasting
confidence: 99%
“…In details, 72.5% in the early adolescents, 81.6% in the middle adolescents, and 86.7% in the late adolescents had long use of electronic devices (Table 4). This is in line with research conducted on adolescents in Banyumas where 88.5% of them showed very high screen time [16]. This indicates that electronic devices by the adolescents were used in more than 2 hours/day for watching television, playing games or playing social media such as TikTok, Facebook, Instagram, WhatsApp, and so on.…”
Section: Relationship Between Screen Viewing Behavior and Nutritional...supporting
confidence: 88%
See 1 more Smart Citation